Sound absorption measurements in plastic-based composites the results obtained with the expression of the statistical equations - (:unkn) unknown (Kaunas University of Technology, 2009)
Sound isolation is a need for human comfort. Products used in every area of our lives against the voice of their behavior are important in the development of products. Also in the car and working environment, producing high sound pressure environment of equipment is run more effectively and economically in the sound isolation needs requires the development of materials. Material in determining the sound absorption rate of the system hardware, software and methods are used. These materials belong to the sound that the system behavior is measured. The purchase of these systems, the establishment, such as calibration features are difficult to counter. This state of the material and spiritual research spending boosts. Researchers need training in this area can not effort to high cost. In this study, resin composite structure in sound absorption coefficient of the standard ASTM E1050-98 to the impedance tube tests as the results were examined statistically. As a result of this study also supports this measure as a model of the 10th polynomial equation was expressed in degrees. With this equation, 192 Hz - 1600 Hz correspond to the frequency, the sound absorption material in the value have been obtained. In this way the researchers want to work on this system without the need of equipment is intended to reach the data.
Keywords: Acoustic; Composite materials; Curve fit; Statsitic